Myocardial antioxidant and oxidative stress changes due to sex hormones - Barp,J. (2002)
The purpose of the present study was to examine myocardial antioxidant and oxidative stress changes in male and female rats in the presence of physiological sex hormone concentrations and after castration. Twenty-four 9-week-old Wistar rats were divided into four groups of 6 animals each: 1) sham-operated females, 2) castrated females, 3) sham-operated males, and 4) castrated males. When testosterone and estrogen levels were measured by radioimmunoassay, significant differences were observed between the castrated and control groups (both males and females), demonstrating the success of castration. Progesterone and catalase levels did not change in any group. Control male rats had higher levels of glutathione peroxidase (50%) and lower levels of superoxide dismutase (SOD, 14%) than females. Control females presented increased levels of SOD as compared to the other groups. After castration, SOD activity decreased by 29% in the female group and by 14% in the male group as compared to their respective controls. Lipid peroxidation (LPO) was assessed to evaluate oxidative damage to cardiac membranes by two different methods, i.e., TBARS and chemiluminescence. LPO was higher in male controls compared to female controls when evaluated by both methods, TBARS (360%) and chemiluminescence (46%). Castration induced a 200% increase in myocardial damage in females as determined by TBARS and a 20% increase as determined by chemiluminescence. In males, castration did not change LPO levels. These data suggest that estrogen may have an antioxidant role in heart muscle, while testosterone does not.